2019
DOI: 10.1007/s13201-019-0993-x
|View full text |Cite
|
Sign up to set email alerts
|

A case study for the assessment of the suitability of gridded reanalysis weather data for hydrological simulation in Beas river basin of North Western Himalaya

Abstract: The major problem of estimating snowmelt runoff for Beas river basin is inadequacy of observed meteorological data distributed across the basin. In this study, ERA-Interim global reanalysis data have been used for assessing the stream flow and sediment yield in Beas river basin of North Western Himalaya. The snow module of ARCSWAT hydrology model has been simulated by integration of subbasin-wise elevation band files for modeling snowmelt runoff process including sediment yield due to rainfall and temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…It is noteworthy that the goal of this study is not to estimate the intrinsic quality of the meteorological forcing (i.e. precipitation and temperature) but rather to understand the impact of the propagation of associated uncertainties on the simulation of hydrological processes (Bhuiyan et al, 2019;Falck et al, 2015;Marthews et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the goal of this study is not to estimate the intrinsic quality of the meteorological forcing (i.e. precipitation and temperature) but rather to understand the impact of the propagation of associated uncertainties on the simulation of hydrological processes (Bhuiyan et al, 2019;Falck et al, 2015;Marthews et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This proves that ERA-Interim reanalysis better represents kinetic precipitation of the Beas river basin. Bhattacharya et al (2019) also found that the rainfall gradient of ERA-Interim is linearly correlated with altitude. The reason may be the ERA-Interim reanalysis product uses a four-dimensional variational (4D-var) analysis model.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore it is necessary to evaluate the precipitation estimates to understand the spatio-temporal distribution of mountain precipitation. Several studies (Bhattacharya et al 2019;Tiwari et al 2018) have reported the advantage of using reanalysis temperature products for snowmelt modeling and simulation of streamflow in high altitude rugged terrain where observation networks are inaccessible. A comparison of various reanalysis temperature estimates with observation is needed to understand the variability of temperature with altitude and to estimate suitable gridded temperature data as a proxy of observation stations for data-limited mountain regions.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of reanalysis products are their spatial and temporal resolution consistency over three or more decades, the large quantity of variables available, and the continuous improvements of their model resolution and biases (Schubert et al 2008;Dee et al 2016). This is why reanalysis products are among the most-used datasets in the study of weather and climate (Fuka et al 2014;Essou et al 2017;Bhattacharya et al 2019;Uniyal et al 2019;Luo et al 2020). However, few studies compared ETo computed using reanalysis data with observed ETo data (Yao et al 2014;Martins et al 2017;Tian et al 2018).…”
Section: Introductionmentioning
confidence: 99%